Dietary Probiotic Supplementation; Effects on Fecundity and Relationship with Biometric Parameters of Clarias gariepinus. - Eyo, Victor Oscar; Ekanem, Albert Philip (Journal of Microbes and Research, 2023)
The implications of probiotics in aquaculture including host health, reproductive development, welfare and nutrition has driven the demand for commercial probiotics for use in aquaculture operations either as feed supplements or through direct application. This study was conducted to evaluate the long-term effects of varying dietary amounts of probiotic supplements on C. gariepinus. Five isonitrogenous diets (42% crude protein) were supplemented with probiotics as follows: Feed A (0 g/kg TPS), Feed B (0.5 g/kg TPS), Feed C (1.0 g/kg TPS), Feed D (1.5 g/kg TPS) and Feed E (2 g/kg TPS) and fed to the experimental fishes in triplicate groups for 38 weeks. Results obtained showed that there was no significant difference in mean fecundity between fish fed the control and probiotic-enriched diets (P > 0.05), with diet B containing 0.5 g/kg Tasly probiotics having the highest fecundity (61,714.00 ± 4,469.43 eggs) and diet C (1.0 g) having the lowest fecundity (49,568.14 ± 3,920.68 eggs). There was a linear relationship between fecundity of Clarias gariepinus with all body parameters such as body weight, ovary weight, and total length and fecundity of female fish. In addition, a positive and significant correlation was obtained between fecundity and all body parameters. Additionally, there was no uniform increase in fecundity with increasing dietary probiotic inclusion level. In conclusion, probiotics supplementation in diets may boost fecundity but increase in probiotic dietary inclusion level will not result in a corresponding increase in fecundity of C. gariepinus.
Keywords: Fecundity; Dietary probiotics supplementation; Relationship; Ovary weight